KEANEKARAGAMAN JENIS AMFIBI (ORDO ANURA) DI KAWASAN HUTAN RUMAH PELANGI SUNGAI AMBAWANG KABUPATEN KUBU RAYA PROVINSI KALIMANTAN BARAT - Slamet Rifanjani; Buhana Panjaitan; Erianto Erianto (Universitas Tanjungpura, 2023)
Rumah Pelangi forest area has an area of 105 ha, made to preserve and maintain the biodiversity in the surrounding environment including types of amphibians. The research aims to record the diversity of natural amphibian (Ordo Anura) species in Rumah Pelangi Forest area. Research using survey method and data collection techniques using Visual Encounter Survey (VES) combined with the transect method. Research results there are 12 species of amphibians (Ordo Anura) in the Rumah Pelangi forest area. Hylarana erythraea was the most common species with an index value of 26.9%. The level species of amphibian diversity (Ordo Anura) is in the medium category with a species diversity index value (H') of 2.07. The dominance index of amphibian spcies is in the low category with a value of 0.1604. The evenness species of amphibian is in the high category with a species evenness index (e) of 0.8330. The similarity species of amphibian is in the very high category with value of 95.6%. Chance ecounter in the Rumah Pelangi forest area with value 3,656 individuals per hour.Keywords: Amphibian, anura, species diversity.AbstrakKawasan hutan Rumah Pelangi memiliki luas 105 ha, dibuat untuk melestarikan dan memelihara keanekaragaman hayati yang ada di lingkungan sekitarnya termasuk jenis-jenis amfibi. Tujuan penelitian ini adalah menganalisis keanekaragaman amfibi (Ordo Anura) di kawasan hutan Rumah Pelangi. Penelitian dengan metode survei dan teknik pengumpulan datanya menggunakan Survei Perjumpaan Visual (VES) dikombinasikan dengan metode jalur. Hasil penelitian terdapat 12 spesies amfibi (Ordo Anura) pada kawasan hutan Rumah Pelangi. Hylarana erythraea merupakan jenis paling banyak dijumpai dengan nilai indeks kelimpahan sebesar 26,9%. Tingkat keanekaragaman jenis amfibi (Ordo Anura) termasuk kategori sedang dengan nilai indeks keanekaragaman jenis (H’) sebesar 2,07. Indeks dominansi jenis amfibi masuk kategori rendah dengan nilai sebesar 0,1604. Kemerataan jenis amfibi masuk kategori tinggi dengan nilai Indeks kemerataan jenis (e) 0,8330. Kesamaan jenis amfibi masuk kategori sangat tinggi dengan nilai sebesar 95,6%. Peluang perjumpaan Anura di kawasan hutan Rumah Pelangi dengan nilai sebesar 3,656 individu/jam.Kata kunci: Amfibi, anura, keanekaragaman jenis.